Is there a connection between specific Jewish human capital and secular achievements of Jews in the USA? - Ritterová, Zuzana (2013)
This diploma thesis shows, that higher incomes of American Jewish people are related to specific factors. The question is if there is some kind of specific human capital which influences Jewish incomes and if there is, how it differs from the common human capital. To find out the answer, the earnings of Jewish men and women and earnings of common Americans without connection to religion will be analyzed. Besides proving the importance and influence of education, other factors, which may increase or decrease the incomes, are also mentioned in the text. This thesis adds to the topic by including analyses of the qualitative data gained by the author; it thus should add to completeness of the research.